2017
DOI: 10.1016/j.celrep.2017.08.071
|View full text |Cite
|
Sign up to set email alerts
|

Culturing CTLs under Hypoxic Conditions Enhances Their Cytolysis and Improves Their Anti-tumor Function

Abstract: Cytotoxic T lymphocytes (CTLs) used in immunotherapy are typically cultured under atmospheric O pressure but encounter hypoxic conditions inside tumors. Activating CTLs under hypoxic conditions has been shown to improve their cytotoxicity in vitro, but the mechanism employed and the implications for immunotherapy remain unknown. We activated and cultured OT-I CD8 T cells at either 1% or 20% O. Hypoxic CTLs survived, as well as normoxic ones, in vitro but killed OVA-expressing B16 melanoma cells more efficientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
96
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 31 publications
12
96
1
1
Order By: Relevance
“…At the tumor site, the effector functions of the CD8 + T cells are facilitated by cytokine production. The effect of hypoxia on each step of the cytolytic function of CD8 + T cells has been studied, with various results (18,23,(26)(27)(28)(29). In this study, we have observed that hypoxia inhibits Ag-specific CD8 + T cell proliferation and effector function.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…At the tumor site, the effector functions of the CD8 + T cells are facilitated by cytokine production. The effect of hypoxia on each step of the cytolytic function of CD8 + T cells has been studied, with various results (18,23,(26)(27)(28)(29). In this study, we have observed that hypoxia inhibits Ag-specific CD8 + T cell proliferation and effector function.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, other in vivo studies demonstrate preferential localization of T cells away from hypoxic tumor zones, suggesting a possible immune escape mechanism used by tumor cells (20)(21)(22). However, some studies have demonstrated that T cells are better killers when activated at lower than normal oxygen conditions (23) and that such cells can enhance tumor rejection (24)(25)(26)(27). Additionally, another study demonstrated increased production of the lytic molecules perforin and granzyme upon constitutive activation of hypoxia inducible factor-1 (HIF-1), the predominate transcription factor for hypoxia signaling, indicating that hypoxic T cells are better killers (28,29).…”
Section: Introductionmentioning
confidence: 96%
“…27,28 Although these molecular mechanisms of how CTLs recognize and kill tumor cells have been characterized in vitro, but little is known about these processes in the living organism especially in the tumor environment. Besides these molecular properties of CTLs, there are various parameters that affect the efficiency of CTLs to eliminate the cancer cells in the complex tumor microenvironment, including the immune suppression environment blocking CTLs to sufficiently infiltrate into the tumor areas and causing CTLs dysfunction, 18,22,29,30 the maximal killing rate of the CTLs in different tissues, 18,23,26,31,32 as well as recognition abilities of CTLs for the target tumor cells. 22,33 Although some correlations have been observed between tumor microenvironment and efficiency of CTLs, the accurate mechanisms of complex parameters that affect the CTLs to induce regression of tumors in vivo are still not known clearly.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless concerns remain about leakiness of gene expression using this approach. Likewise, antigen-specific CD8 + T-cells expanded in hypoxic conditions prior to adoptive cell transfer have been shown to exhibit greater intrinsic effector function due to higher concentrations of granzyme B in their cytolytic granules[91].Universal modular CAR designsM A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPTVarious customizable CAR platforms have been designed to reduce the financial and human costs associated with the development of individual antigen-targeting CARs. Such approaches are particularly welcome in anticipation of the development of "off the shelf" allogeneic CAR products.…”
mentioning
confidence: 99%
“…mutation of the Lck-binding site in CD28 may reduce IL-2 production & minimize Treg expansion); the extracellular scFv may be substituted with targeting moieties derived from endogenous molecules (e.g. the pan-ErbB ligand, T1E[90] or NKG2D[91]), single domain nanobodies or monomeric fibronectin-based domains; adjustments to the spacer and/or transmembrane domain may also impact upon efficacy. (B) Expression of surface costimulatory molecules: examples include chimeric cytokine receptors (e.g.…”
mentioning
confidence: 99%